2016
DOI: 10.1002/psc.2901
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the SH3 domain of human osteoclast‐stimulating factor with rationally designed peptoid inhibitors

Abstract: Human osteoclast-stimulating factor (hOSF) is an intracellular protein produced by osteoclasts that induces osteoclast formation and bone resorption. The protein contains a modular Src homology 3 (SH3) domain that mediates the intermolecular recognition and interaction of hOSF with its biological partners. Here, we proposed targeting the hOSF SH3 domain to disrupt hOSF-partner interactions for bone disease therapy by using SH3 inhibitors. In the procedure, the primary sequences of three known hOSF-interacting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The OSF can interact with an array of its cognate protein partners through its SH3 domain to orchestrate cellular signaling networks. Previously, Han et al identified 3 interacting partners of OSF SH3 domain, ie, proto‐oncogene tyrosine‐protein kinase ( c ‐Src); survival motor neuron (SMN); and Src‐associated in mitosis, 68 kD (Sam68), from which totally 31 octapeptide segments that contain linear polyproline motif PXXP recognized by SH3 domain were determined . Considering that the CICSR‐based QSAR model built in this study was based on SH3‐binding decapeptide ligands, we herein extended these 8‐ to 10‐mer peptides by adding a residue separately at N‐ and C‐termini of each peptide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OSF can interact with an array of its cognate protein partners through its SH3 domain to orchestrate cellular signaling networks. Previously, Han et al identified 3 interacting partners of OSF SH3 domain, ie, proto‐oncogene tyrosine‐protein kinase ( c ‐Src); survival motor neuron (SMN); and Src‐associated in mitosis, 68 kD (Sam68), from which totally 31 octapeptide segments that contain linear polyproline motif PXXP recognized by SH3 domain were determined . Considering that the CICSR‐based QSAR model built in this study was based on SH3‐binding decapeptide ligands, we herein extended these 8‐ to 10‐mer peptides by adding a residue separately at N‐ and C‐termini of each peptide.…”
Section: Resultsmentioning
confidence: 99%
“…Short polyproline peptide segments have been widely used as the OSF SH3 ligands, as they can mimic the interacting sites of the domain's cognate partner proteins. However, these peptides show a broad specificity and high cross‐reactivity when binding to the domain, largely limiting the application of designing therapeutic peptides to disrupt the peptide‐mediated interactions of between human OSF and its partners in SO therapy . Recently, computational modeling and statistical analysis have been widely used to characterize the binding behavior and energetics of peptide ligands to their cognate domain receptors .…”
Section: Introductionmentioning
confidence: 99%
“…A total of 1472 peptides with known binding potency to SH3 domain were collected from the literatures and databases, from which we only selected those of 8 amino acids long (octopeptides) with determined affinity values and, consequently, 573 samples were extracted for further analysis. Compared to other public databases, this is a much more homogenous set of data, as all of it was generated in 1 of only 2 assay systems.…”
Section: Methodsmentioning
confidence: 99%
“…A combination of template‐directed peptide grafting and virtual mutagenesis described in our previous work was used to computationally model the complex structures of hOSF SH3 domain with its peptide ligands. First, the primary sequence of hOSF SH3 domainwas retrieved from the UniProt database with code Q92882, which was searched against the PDB database by using NCBI BLAST server to identify those homologous SH3 domains in complex with peptide ligands.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation